BID’AH DALAM KAJIAN HADIS - Nurliana Damanik (UIN Sumatera Utara Medan, 2022)
Bid'ah is creating and starting something for the first time and there is no related experience about that. It can be interpreted as a path in religion that is made up (without any evidence or instructions) resembles the Syariat (Islamic teachings). This type of research is library research using the hadith approach. In obtaining the data, several studies of hadith related to the views of scholars regarding bid'ah are presented. Regarding to this interpretation, it was found that first, bid'ah is an act that is prohibited in Islamic teachings because bid'ah is additions in terms of aqidah and worship that are not contained in Islamic law. Second, heresy is Al-Ikhdas, which is making up something new that has no previous example. Third, something new is based on religion, meaning that an act that is made up is connected with religious teachings and the perpetrator believes in.